If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 6(t + -4) = 4(t + -6) + 8 Reorder the terms: 2 + 6(-4 + t) = 4(t + -6) + 8 2 + (-4 * 6 + t * 6) = 4(t + -6) + 8 2 + (-24 + 6t) = 4(t + -6) + 8 Combine like terms: 2 + -24 = -22 -22 + 6t = 4(t + -6) + 8 Reorder the terms: -22 + 6t = 4(-6 + t) + 8 -22 + 6t = (-6 * 4 + t * 4) + 8 -22 + 6t = (-24 + 4t) + 8 Reorder the terms: -22 + 6t = -24 + 8 + 4t Combine like terms: -24 + 8 = -16 -22 + 6t = -16 + 4t Solving -22 + 6t = -16 + 4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4t' to each side of the equation. -22 + 6t + -4t = -16 + 4t + -4t Combine like terms: 6t + -4t = 2t -22 + 2t = -16 + 4t + -4t Combine like terms: 4t + -4t = 0 -22 + 2t = -16 + 0 -22 + 2t = -16 Add '22' to each side of the equation. -22 + 22 + 2t = -16 + 22 Combine like terms: -22 + 22 = 0 0 + 2t = -16 + 22 2t = -16 + 22 Combine like terms: -16 + 22 = 6 2t = 6 Divide each side by '2'. t = 3 Simplifying t = 3
| y+4-4=3x-9-4 | | 4q+6=-3q-43 | | -2m+7=2m-1 | | 5h=4x | | 8e-3=5e-9 | | 17d-3=9d+45 | | 2p+9=6p-27 | | 9t+10t=38 | | -c+2=-6c-13 | | 654/15 | | -2w+1=-7w+41 | | 5h=3x+150 | | -2f-6=-5f-3 | | 11d+5=3d-3 | | 7z-6=3z+4 | | -8k+4=-6k+20 | | 9j-4=5j+28 | | -6u+7=u+70 | | y/5=-20 | | 11u+1=6u-29 | | -x-4=-4x+2 | | -8g+7=-g+63 | | 70=6x-14 | | 7j-4=3j-28 | | 10e-4=4e-10 | | 2a+4=-3a-36 | | -2q+6=3q-24 | | 2x-1=-x-28 | | 6h-4=h-9 | | 9y-1=5y+15 | | 12+8=5d+57 | | 7(3g+8)/4=35 |